Worm hole filling material for wood component, preparation method and application
By combining pectin with log wood chips and adding water-based polyurethane and boride, a wood component wormhole filling material with excellent performance was prepared, which solved the problems of low bonding strength, low stability and poor durability of existing materials, and achieved efficient and environmentally friendly wormhole filling and repair effect.
Patent Information
- Application Number
- CN202510016951.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-08
AI Technical Summary
The existing wooden ancient building wormhole filling materials have low bond strength, low stability and poor durability, resulting in unsatisfactory filling effect and cannot meet the requirements of long-term protection.
Using pectin combined with log wood chips and adding water-based polyurethane and borides to prepare a wormhole filling material for wood components. Through specific ratios and processes, the bond strength, stability and durability of the material are improved.
It achieves high bond strength, stability and durability, can effectively fill wormholes, maintain the natural properties of the wood, and has good anti-mold and insect resistance.
Smart Images

Figure CN119775959A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cultural relics protection, and relates to a wormhole filling material for a wooden component, a preparation method and an application thereof. Background Art
[0002] Ancient wooden buildings are an important part of traditional Chinese architecture and are famous for their long history, exquisite craftsmanship and rich cultural connotations. Typical ancient wooden buildings include palaces, temples, towers and traditional houses, all of which reflect the wisdom and artistic achievements of ancient Chinese architecture; these buildings are mostly designed with complex wooden structures, with high aesthetic value and technical level. However, due to long-term exposure to the natural environment and human influence, ancient wooden buildings are threatened by various diseases, among which insect pests are particularly prominent. At present, ancient wooden buildings are susceptible to erosion by pests such as termites, carpenter bees, longhorn beetles and wood-boring beetles in humid and warm environments, resulting in a decrease in the safety of wooden structures, and then the surface decoration of wooden structures (such as carvings and paintings) is damaged. Therefore, filling and repairing the wormholes formed by insect erosion in ancient wooden buildings is a key to the protection of ancient wooden buildings.
[0003] At present, the technology for filling and repairing wormholes in ancient wooden buildings is relatively backward, and there is a lack of effective methods. Among the technologies that have been adopted, gypsum is generally used to fill wormholes. Although this method is simple to operate and low-cost, due to the mismatch between gypsum and wood in physical and chemical properties, the filled parts are prone to cracks or fall off due to changes in humidity and temperature, and may even cause secondary damage. In addition, when repairs are needed later, gypsum fillings are difficult to remove; moreover, gypsum also lacks mildew and insect-proof properties, and cannot effectively inhibit the recurrence of insect pests in a humid environment; what's worse, white spots remain after gypsum filling, which is difficult to match with the color of the painted on the wooden components, causing damage to the artistic value.
[0004] In order to improve the problems existing in the existing plaster filling, researchers have tried to use a mixture of gelatin and sawdust as a filling material in recent years. Although gelatin is compatible with wood, in practical applications, the low bonding strength of gelatin before the gel state cannot be used to fill and repair wooden ancient buildings. When filling downward wormholes, the low bonding strength makes it difficult to operate. In addition, after filling, the stability and durability are low in a high humidity environment, resulting in mildew within a few days, which leads to unsatisfactory repair effects and cannot meet the requirements for long-term protection of wooden ancient buildings.
[0005] Therefore, there is an urgent need to find a wormhole filling material for ancient wooden buildings with better performance to address the deficiencies in the existing technology. Summary of the invention
[0006] In view of the technical problems of low bonding strength, low stability and poor durability in the above-mentioned existing filling and repair of ancient wooden buildings, the present invention provides a wormhole filling material for wooden components, a preparation method and application.
[0007] The present invention adopts pectin combined with log sawdust and adds water-based polyurethane to form a wood component wormhole filling material, which has high bonding strength and improves stability and durability in a hot and humid environment.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] A wood component wormhole filling material is made of sawdust, pectin, waterborne polyurethane and boride, wherein the mass fraction of the sawdust is 50% to 60%; the mass fraction of the pectin is 35% to 40%; the mass fraction of the waterborne polyurethane is 1% to 5%; and the mass fraction of the boride is 1% to 5%.
[0010] It is further defined that the mass fraction ratio of the sawdust to the pectin is 3:2.
[0011] It is further defined that the mass fraction of the sawdust is 54%; the mass fraction of the pectin is 36%; the mass fraction of the waterborne polyurethane is 5%; and the mass fraction of the boride is 5%.
[0012] It is further defined that the pectin is at least one of gum arabic, peach gum and orange peel gum among plant pectins; and the boride is disodium octaborate or borax.
[0013] A method for preparing the wood component wormhole filling material comprises the following steps:
[0014] S1. Stirring and mixing sawdust and pectin in a container in accordance with the mass fractions of claim 1 to obtain a mixture;
[0015] S2. Weigh the waterborne polyurethane and the boride according to the mass fractions described in claim 1, and then dissolve them in water to obtain a mixed solution; the mass of the water is twice the total weight of the wormhole filling material of the wooden component;
[0016] S3, pouring the mixed solution in step S2 into the mixture in step S1, stirring evenly, to obtain.
[0017] The application of the wood component wormhole filling material in wormhole filling.
[0018] The application of the wood component wormhole filling material in filling wormholes in ancient wooden buildings.
[0019] It is further defined that, in application, bamboo chopsticks are used to apply external force to stuff the wormhole filling material of the wooden component into the wormhole according to the diameter of the wormhole, and the filling is completed by curing for 24h to 48h under the conditions of temperature of 10℃ to 25℃ and humidity of 20% to 50%.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention innovatively uses plant-derived pectin as the main component, combined with log sawdust, boride and water-based polyurethane, to prepare a filling material with good chemical compatibility with wood materials. Pectin, as a natural plant extract, is more compatible with wood (plant material) in molecular structure, can penetrate wood fibers deeply, form a tight bond, and has excellent bonding strength, elasticity and compatibility; boride and water-based polyurethane are introduced into the pectin-sawdust composite system, and boride inhibits the enzyme system and cell metabolism of fungi by releasing boron ions, while interfering with the development of insects and producing a toxic effect, thereby giving the material good mildew and insect-proof properties; water-based polyurethane enhances the three-dimensional network structure of pectin through chemical cross-linking, significantly improving the interfacial bonding force and mechanical properties of the material; the introduction of flexible molecular chains improves the toughness of the material, and the effect of hydrophobic groups reduces the sensitivity of the material to humid and hot environments, further improving the environmental stability and durability of the filling material.
[0022] 2. In the present invention, the filling material formed by pectin and sawdust not only fills the wormhole defects, but also retains the natural properties of the wood, achieving an environmentally friendly and efficient filling and repairing effect.
[0023] 3. The present invention has found through research that, compared with the original wood material, the wood component wormhole filling material has small color difference and small roughness after filling. The wood component wormhole filling material has good compatibility with wood and good filling effect, and has great application prospects in the filling and repair of wormholes in wooden ancient buildings. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 It is a line graph of the mechanical properties test of the filling materials provided in Example 1 and Comparative Example 2, wherein Figure (a) is a line graph of the bonding strength test of Sample 2 made of two filling materials after aging for 120 hours; Figure (b) is a line graph of the compression test of Sample 1 made of two filling materials after aging for 120 hours;
[0026] Figure 2 are two groups of reflectance graphs of reflected light of sample 2 prepared from the filling materials provided in Example 1 and Comparative Example 2;
[0027] Figure 3 The results of laser confocal microscopy of the interface between the filling surface and the original wood surface of the sample 2 made of the filling material provided in Example 1, wherein Figure (a) is an original micrograph of the divided and marked area; Figure (b) is a three-dimensional fitting diagram of the surface of the area in Figure (a);
[0028] Figure 4 The present invention is a scanning electron microscope image and an energy spectrum result image of the filling area and the original wood area of the sample 2 made of the filling material of Example 1; wherein: Figure (a) is a scanning electron microscope image of the junction of the two areas at 50 times magnification; Figure (b) is a scanning electron microscope image of the filling area in Figure (a) at 300 times magnification; Figure (c) is a scanning electron microscope image of the original wood area in Figure (a) at 300 times magnification; Figure (d) is a scanning electron microscope image of the local area in Figure (b) at 1000 times magnification; Figure (e) is a diagram of the energy spectrum test result in Figure (d); Figure (f) is an element distribution diagram of the energy spectrum test surface scan in Figure (d);
[0029] Figure 5 Observation diagrams of the test records of the mold test of the filling materials provided in Example 1 and Comparative Example 3 before and after aging; wherein: Figure (a1) is the mold resistance test result of Aspergillus niger before aging; Figure (a2) is the mold resistance test result of Aspergillus flavus before aging; Figure (a3) is the mold resistance test result of Penicillium citrinum before aging; Figure (a4) is the mold resistance test result of Trichoderma before aging; Figure (b1) is the mold resistance test result of Aspergillus niger after aging; Figure (b2) is the mold resistance test result of Aspergillus flavus after aging; Figure (b3) is the mold resistance test result of Penicillium citrinum after aging; Figure (b4) is the mold resistance test result of Trichoderma after aging;
[0030] Figure 6 These are scanning electron microscope photos of samples of mold tests before aging of the filling materials provided in Example 1 and Comparative Example 3; wherein: Figure (a1) is a sample surface with Aspergillus niger growing at 200 times; Figure (a2) is a sample photo without Aspergillus niger growing at 200 times; Figure (b1) is a sample surface with Aspergillus flavus growing at 200 times; Figure (b2) is a sample photo without Aspergillus flavus growing at 200 times; Figure (c1) is a sample surface with Penicillium citrinum growing at 1000 times; Figure (c2) is a sample photo without Penicillium citrinum growing at 1000 times; Figure (d1) is a sample surface with Trichoderma growing at 1000 times; Figure (d2) is a sample photo without Trichoderma growing at 1000 times. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is now described in detail with reference to the accompanying drawings and embodiments.
[0032] The technical idea of the present invention is to use sawdust to simulate the strength and elasticity provided by cellulose and hemicellulose in wood; use pectin to simulate the bonding effect of lignin, and then add water-based polyurethane to enhance mechanical properties and boron to prevent mildew and insects; each raw material works synergistically in a specific ratio to enhance the binding force and bonding strength of the filling material and the wooden components, as well as the stability and durability in humid and hot environments.
[0033] The main components of wood include cellulose, hemicellulose and lignin, which together constitute the basic structure and physical properties of wood. Cellulose is a long-chain polysaccharide composed of glucose monomers, accounting for about 40-50% of the dry weight of wood, and mainly provides the strength and hardness of wood; hemicellulose is a more complex class of short-chain polysaccharides, accounting for 20-30% of the dry weight of wood. Hemicellulose combines with cellulose to give wood better elasticity. Lignin plays a vital role as a "binder" in wood, accounting for 15-40% of the dry weight of wood. Lignin binds cellulose and hemicellulose tightly together, giving wood greater durability and stability. In addition, wood also contains non-structural substances such as resins, fatty acids, and waxes, which account for about 10% of the dry weight of wood.
[0034] A wood component wormhole filling material is made of sawdust, pectin, waterborne polyurethane and boride, wherein the mass fraction of sawdust is 50% to 60%, the mass fraction of pectin is 35% to 40%, the mass fraction of waterborne polyurethane is 1% to 5%, and the mass fraction of boride is 1% to 5%.
[0035] In the present invention, the mass fraction ratio of sawdust to pectin is 3:2.
[0036] Preferably, the mass fraction of sawdust is 54%; the mass fraction of pectin is 36%; the mass fraction of waterborne polyurethane is 5%; and the mass fraction of boride is 5%.
[0037] Preferably, the pectin is at least one of gum arabic, peach gum and orange peel gum among plant pectins; and the boride is disodium octaborate or borax.
[0038] The present invention provides a method for preparing a wood component wormhole filling material, comprising the following steps:
[0039] S1. Stir and mix the sawdust and pectin in a container according to the above mass fractions to obtain a mixture;
[0040] S2. Weigh the waterborne polyurethane and the boride according to the above mass fractions respectively, and then dissolve them in water to obtain a mixed solution; the mass of the water is twice the total weight of the wormhole filling material of the wooden component;
[0041] S3, pouring the mixture in step S1 into the mixed solution in step S2, stirring evenly, to obtain.
[0042] The wood component wormhole filling material proposed by the present invention can be used for filling wormholes, especially for filling wormholes in wooden ancient buildings. In application, according to the diameter of the wormhole, a bamboo chopstick is used to apply external force to insert the wood component wormhole filling material into the wormhole. Under the conditions of temperature of 10°C to 25°C and humidity of 20% to 50%, the curing time should be 24h to 48h to complete the filling.
[0043] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0044] It should be noted that, unless otherwise specified, the chemicals and reagents used in the following examples are all conventional commercial products in the art.
[0045] It should be noted that, unless otherwise specified, the operations used in the following embodiments are all conventional operations in the art. For example, if the temperature is not specified, it means room temperature.
[0046] Example 1
[0047] This embodiment provides a wood component wormhole filling material, which is composed of wood chips, pectin, water-based polyurethane and boride.
[0048] In this embodiment, the mass fraction of sawdust is 54%; the mass fraction of pectin is 36%; the mass fraction of waterborne polyurethane is 5%; and the mass fraction of boride is 5%.
[0049] Preferably, the wood chips are of the same kind as the wood components to be filled according to actual needs.
[0050] The pectin is plant pectin, specifically at least one kind of gum arabic.
[0051] Preferably, the waterborne polyurethane is a one-component waterborne polyurethane.
[0052] Preferably, the boride is disodium octaborate (Na2B8O 13 ·4H2O).
[0053] In this embodiment, the method for preparing the wood component wormhole filling material comprises the following steps:
[0054] S1. Stir and mix the sawdust and pectin in a container according to the above mass fractions to obtain a mixture;
[0055] S2. Weigh the waterborne polyurethane and the boride according to the above mass fractions respectively, and then dissolve them in water to obtain a mixed solution; the mass of the water is twice the total weight of the wormhole filling material of the wooden component;
[0056] S3, pouring the mixture in step S1 into the mixed solution in step S2, stirring evenly, to obtain.
[0057] Example 2
[0058] This embodiment provides a wood component wormhole filling material, which is composed of wood chips, pectin, water-based polyurethane and boride.
[0059] In this embodiment, the mass fraction of sawdust is 54%; the mass fraction of pectin is 38%; the mass fraction of waterborne polyurethane is 3%; and the mass fraction of boride is 5%.
[0060] In this embodiment, the preparation method of the wood component wormhole filling material is the same as that in Embodiment 1.
[0061] Example 3
[0062] This embodiment provides a wood component wormhole filling material, which is composed of wood chips, pectin, water-based polyurethane and boride.
[0063] In this embodiment, the mass fraction of sawdust is 54%; the mass fraction of pectin is 40%; the mass fraction of waterborne polyurethane is 1%; and the mass fraction of boride is 5%.
[0064] In this embodiment, the preparation method of the wood component wormhole filling material is the same as that in Embodiment 1.
[0065] Taking the wood component wormhole filling materials prepared in Examples 1 to 3 as examples, experiments were conducted to verify the performance of the wood component wormhole filling materials.
[0066] In order to illustrate the superiority of the performance of the wormhole filling material for wooden components of the present invention, a comparative example was also designed in the experimental verification.
[0067] Comparative Example 1
[0068] This comparative example provides a wood component wormhole filling material, which is composed of wood chips, pectin and boride.
[0069] In this embodiment, the mass fraction of sawdust is 55%; the mass fraction of pectin is 40%; and the mass fraction of boride is 5%.
[0070] In this comparative example, the preparation method of the wood component wormhole filling material is the same as that in Example 1.
[0071] Comparative Example 2
[0072] In this embodiment, the mass fraction of sawdust is 60%; the mass fraction of gelatin is 40%.
[0073] Comparative Example 3
[0074] This comparative example provides a wood component wormhole filling material, which is composed of wood chips, pectin and water-based polyurethane.
[0075] In this embodiment, the mass fraction of sawdust is 55%; the mass fraction of pectin is 40%; and the mass fraction of waterborne polyurethane is 5%.
[0076] In this comparative example, the preparation method of the wood component wormhole filling material is the same as that in Example 1.
[0077] The performance of the wood component wormhole filling materials in the above-mentioned embodiments and comparative examples was further investigated and studied through the filling material physical properties, mildew resistance test and filling test.
[0078] 1. Make a simulation sample
[0079] (1) After the filling material is prepared, it is immediately placed in the corresponding mold to prepare a 20 mm × 20 mm × 20 mm sample. After it is solidified, it is taken out and recorded as sample 1 for studying the compressive strength of the filling material.
[0080] (2) A rectangular wooden block with a size of 40mm×15mm×30mm is used, and a small hole with a diameter of 8±0.5mm and a depth of no more than 30mm is drilled. The holes are filled and repaired using the repair material prepared in the above method and the above method. After complete drying, the block is cut along the cross section to produce a simulated filling sample, which is recorded as sample 2; it is used to simulate the filling and repair of wormholes by filling materials. Among them, when filling sample 2, a bamboo stick corresponding to the diameter of the wormhole is used, and the bamboo chopsticks apply external force to insert the prepared filling material into the wormhole to complete the filling; the filling conditions are: room temperature 10℃~25℃, humidity 20%~50%, and curing time is 24h~48h; after the filling material is cured, it is judged whether it needs to be refilled according to the actual shrinkage situation. If necessary, it is carried out according to the above filling method.
[0081] (3) Prepare a bonding area of 20 mm × 20 mm × 2 mm between two wood pieces and use the prepared sample to bond them. After solidification, it is recorded as sample 3; it is used to study the bonding strength and shear strength of the filling material.
[0082] (4) A sample piece of 20 mm × 20 mm × 2 mm was prepared and taken out after solidification. It was recorded as sample 4 and used to study the anti-mildew performance of the filling material.
[0083] 2. Experimental characterization results and discussion
[0084] 2.1. Filling material performance test
[0085] 2.1.1 Shrinkage
[0086] The filling materials of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 were taken respectively, and five sample blocks were obtained according to the preparation method of Sample 1, and then a shrinkage test was performed. The test method of the shrinkage rate refers to LY / T 2490-2015.
[0087] The shrinkage test results are shown in Table 1.
[0088] Table 1 Shrinkage test results
[0089]
[0090] As can be seen from Table 1, the shrinkage rate of the filling material formed by gelatin sawdust in Comparative Example 2 is 12.239%; the shrinkage rate of the filling material formed by pectin, sawdust and boride in Comparative Example 1 is 4.931%; and the shrinkage rate of the filling material formed by pectin, sawdust, water-based polyurethane and boride in Examples 1 to 3 is 4.735% to 5.752%. It can be seen that compared with the gelatin in Comparative Example 2, the shrinkage rate after using pectin is significantly lower, indicating that the use of pectin can greatly reduce the shrinkage rate; at the same time, compared with Comparative Example 1, the shrinkage rate of Examples 1 to 3 does not change much, indicating that whether or not to add water-based polyurethane has no significant effect on the shrinkage rate of the sample block, and the main role in reducing the shrinkage rate is due to the addition of pectin. It can be seen that the addition of pectin has a lower shrinkage rate than the existing gelatin filling material.
[0091] 2.1.2 Stress test
[0092] The filling materials of Example 1, Example 2, Example 3 and Comparative Example 1 were respectively taken, and four sample blocks were obtained according to the preparation method of Sample 1, and then a compression test was performed. The compression test method refers to GB / T1927.11-2022.
[0093] The filling materials of Example 1, Example 2, Example 3 and Comparative Example 1 were respectively taken, and four sample blocks were obtained according to the preparation method of Sample 3, and then a shear test was performed. The shear test method refers to GB / T33333-2016.
[0094] The results of the compression test and shear test are shown in Table 2.
[0095] Table 2 Stress test results
[0096]
[0097] According to the test results in Table 2, compared with Comparative Example 1 without adding waterborne polyurethane, the compressive strength and shear strength of Examples 1 to 3 are improved after adding waterborne polyurethane, indicating that the addition of waterborne polyurethane greatly increases the mechanical properties of the filling material. At the same time, it can be seen from the data of Examples 1 to 3 that the compressive strength and shear strength both show an upward trend with the increase in the amount of waterborne polyurethane added, indicating that the mechanical properties of the filling material are positively correlated with the amount of waterborne polyurethane added.
[0098] 2.1.3. Bond strength and compressive strength
[0099] Take the two filling materials in the above-mentioned Example 1 and Comparative Example 2, respectively, and obtain Sample 1 and Sample 2 according to the above-mentioned preparation method, and then perform mechanical tests again on the samples after wet heat aging. The results are as follows: Figure 1 shown.
[0100] from Figure 1 It can be seen that after wet heat aging, the mechanical properties of the samples made of the two filling materials have decreased to varying degrees. On the third day of aging, it can be found that the compressive properties of the gelatin filling material have decreased significantly, and the bonding strength has also decreased significantly. This is because wet heat aging is a high-low temperature cycle and a high-low humidity cycle, and the high-temperature cycle of gelatin will cause the secondary structure (such as α-helix or β-fold) in the gelatin molecule to gradually loosen and denature, so that the hydrogen bonds in it will break, causing the structure to lose stability.
[0101] The filling material of Example 1 is added with water-based polyurethane and pectin, and its aging resistance is better than gelatin, and the mechanical properties decrease slowly; this is because the reinforcing effect of water-based polyurethane has a good effect on improving the moisture resistance and thermal stability of the pectin system; at the same time, polyurethane itself has strong water resistance and heat resistance, and can form stronger intermolecular interactions with pectin molecules, thereby improving its mechanical properties during aging. In addition, the introduction of polyurethane improves the interfacial adhesion between pectin and the wood surface, so that the bonding strength remains at a high level under a hot and humid environment. Therefore, adding polyurethane to pectin, wood chips and boride not only improves the aging resistance of pectin, but also enhances its stability in long-term use.
[0102] 2.2. Simulation filling test
[0103] 2.2.1、Color difference test
[0104] Take the filling materials of Example 1 and Comparative Example 2 respectively, and obtain two sample blocks according to the preparation method of Sample 2, and perform color difference test. The test method is: UNE-EN 15886. Specifically, the color difference values of the original wood block area (area 1) and the filling area (area 2) are tested. The test results are Figure 2shown.
[0105] from Figure 2 From the reflection graph results, we can see that the degree of light reflection in the filled area is slightly lower than that in the original area, which means that it absorbs some colors, so the color it shows should be darker. The two sets of data are shown in Table 3.
[0106] Table 3 Color difference test parameters
[0107]
[0108] From the data in Table 3, it can be seen that compared with Comparative Example 2, the filling material provided in Example 1 has a L * 、a * 、b * The values of ΔE of the filling area of the filling material of Example 1 are closer to the values of the corresponding indicators of the original wood block area. * This indicates that the filling material provided by Example 1 has a smaller color difference than the original wood block, a smaller degree of color change, better compatibility with the original wood block material, and a better filling effect.
[0109] 2.2.2 Roughness test
[0110] According to the method of Sample 2, the wood hole filling material of the wooden component prepared in Example 1 is used to fill the wood holes of the complete wooden block. After it is dried, it is cut along its cross section, and the surface roughness of the wood hole filling area (area 2) and the area of the original wooden block (area 1) is observed using a laser confocal scanning microscope.
[0111] Figure 3 It is a scanning micrograph of a certain area at the junction of the filled area and the intact area. Two rectangular parts of equal area were selected in two different areas (area 1 and area 2), and the surface roughness data were analyzed separately. The analysis data are listed in Table 3.
[0112] Table 3 Roughness parameter results of two regions
[0113] Roughness parameters Sa S Str Spc Sdn Region 1 12.467 129.964 0.306 5852.177 8.192 Area 2 15.736 115.941 0.345 7005.054 11.370
[0114] The data in Table 3 show that the roughness value of the original wood block area (area 1) is small, while the roughness parameter of the filling area (area 2) is relatively close to the original wood block area, indicating that the roughness of the simulated filling area is small; at the same time Figure 3 It can be seen intuitively in the three-dimensional display diagram that the roughness of the two areas is slightly different, indicating that after the holes are filled with the filling material of the present invention, the compatibility with the original wood block is higher.
[0115] 2.2.3 Scanning electron microscopy observation and analysis
[0116] Take the sample of the roughness test above, take photos and observe with a scanning electron microscope, and scan its elements with an energy spectrum analyzer using a scanning electron microscope. The results are as follows: Figure 4 shown.
[0117] Figure 4 (a) is the junction of the sample filling area and the original wood area observed at 50 times. The two parts were magnified to 300 times and photographed separately, as shown in the figure below. Figure 4 (b) is the image of the filled area observed at 300 times. Figure 4 (c) is an image of the original wood area observed at 300 times. The filled area is further magnified to 1000 times. Figure 4 As shown in (d), it can be observed that the enlarged material is mainly a network substance, which is a network of polysaccharide fibers formed after the pectin loses water. This shows that the addition of pectin can improve the mechanical properties and bonding properties of the filling material.
[0118] The results of energy spectrum analysis are as follows Figure 4 As shown in (e), C and O are the main elements. The slightly lower content of Au is the residue of the gold spraying process when using the scanning electron microscope to prepare the sample. Figure 4 (f) shows Figure 4 (d) The red element is the position mark of the C element, and the blue element is the position mark of the O element. It can be found that the element distribution at the same height is very uniform. This shows that the distribution of pectin in the filling material is relatively uniform, which further shows that the filling method can bring the filling material to the best effect.
[0119] 2.3. Anti-mildew test
[0120] The molds used in the mildew prevention experiment (including Aspergillus niger, Aspergillus flavus, Penicillium citrinum and Trichoderma) were collected from Baoen Temple and cultured in the laboratory. The wood component wormhole filling materials prepared in Example 1 and Comparative Example 3 were used to make two simulation blocks according to Sample 4.
[0121] The test method is: use an inoculation stick to scrape the hyphae and spores of the mold, and evenly disperse them in 20ml of physiological saline to form a suspension containing fungal spores. Then, soak the dried samples 4 in the suspension for 1 minute to evenly cover the surface of the simulated sample with the bacterial solution. After the surface of the simulated sample is slightly dried, put it in the PDA culture medium to observe the growth of the mold to verify the anti-mold effect of the filling material with boride. The photo of the culture medium after 5 days of mold growth is as follows Figure 5 As shown (before aging); further, after the two simulated samples were aged for 120 hours, the mildew resistance test was performed again. The test results of the culture medium after 5 days of mildew growth are shown in the figure. Figure 5 (after aging).
[0122] See also Figure 5 Before aging, the filling material on the left side of the culture medium without boride was covered with mold and hyphae, and mold also grew around it, while the filling material on the right side after adding boride had no mold growth observed. This shows that the addition of boride makes the filling material anti-mold.
[0123] See also Figure 5 After aging, the results were consistent with the mildew resistance test results before aging. The aged samples still had mildew resistance and could effectively prevent and control the four types of mildew at the Baoen Temple site. This is because the water solubility of boride enables it to diffuse into the wood and form a long-term protective layer by releasing B 3+ , B 4+ Inhibits the enzyme system and cell metabolism of fungi, while borides can interfere with the development of insects and have a toxic effect.
[0124] To further analyze the mold situation on the surfaces of the two simulated samples, a scanning electron microscope (SEM) was used to observe the surfaces of the two simulated samples. Figure 6 shown.
[0125] Figure 6 The results showed that the hyphae structure with fungal morphological characteristics was clearly visible on the surface of the simulated sample without boron compound. The surface of the untreated sample had fungal hyphae and spores, while no fungus was found in the samples in the control group.
[0126] The above anti-mildew test results show that the anti-mildew effect of the wood component wormhole filling material after adding boride is significant.
[0127] The above bonding strength, compressive strength, simulated filling test and mildew resistance test all adopt the wood component wormhole filling material prepared in Example 1. When the above tests are carried out with the wood component wormhole filling materials of Example 2 and Example 3, the performance they exhibit is similar to the material performance of Example 1, and both have very high bonding strength, mechanical properties, and improve the environmental stability and durability of the filling material.
[0128] In Example 1, the mass fraction of sawdust can be arbitrarily replaced within 50% to 60%; the mass fraction of pectin can be arbitrarily replaced within 35% to 40%; the mass fraction of waterborne polyurethane can be arbitrarily replaced within 1% to 5%; the mass fraction of boride can be arbitrarily replaced within 1% to 5%. When pectin is selected from peach gum, orange peel gum, or two or more of gum arabic, peach gum and orange peel gum; when the boride is borax, the prepared wood component wormhole filling material also exhibits properties similar to those of the material in Example 1.
[0129] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A wood component wormhole filling material, characterized in that: The invention is made of sawdust, pectin, waterborne polyurethane and boride, wherein the mass fraction of the sawdust is 50% to 60%, the mass fraction of the pectin is 35% to 40%, the mass fraction of the waterborne polyurethane is 1% to 5%, and the mass fraction of the boride is 1% to 5%.
2. The wood component wormhole filling material according to claim 1, characterized in that: The mass fraction ratio of the sawdust to the pectin is 3:
2.
3. The wood component wormhole filling material according to claim 2, characterized in that: The mass fraction of the sawdust is 54%; the mass fraction of the pectin is 36%; the mass fraction of the waterborne polyurethane is 5%; and the mass fraction of the boride is 5%.
4. The wood component wormhole filling material according to claim 1, characterized in that: The pectin is at least one of gum arabic, peach gum and orange peel gum in plant pectin; the boride is disodium octaborate or borax.
5. A method for preparing the wood component wormhole filling material according to claim 1, characterized in that: The following steps are involved: S1. Stirring and mixing sawdust and pectin in a container in accordance with the mass fractions of claim 1 to obtain a mixture; S2. Weigh the waterborne polyurethane and the boride according to the mass fractions described in claim 1, and then dissolve them in water to obtain a mixed solution; the mass of the water is twice the total weight of the wormhole filling material of the wooden component; S3, pouring the mixed solution in step S2 into the mixture in step S1, stirring evenly, to obtain.
6. Use of the wood component wormhole filling material as claimed in claim 1 in wormhole filling.
7. Use of the wood component wormhole filling material as claimed in claim 1 in filling wormholes in ancient wooden buildings.
8. The use according to claim 6 or 7, characterized in that: In application, according to the diameter of the wormhole, bamboo chopsticks are used to apply external force to stuff the wormhole filling material of the wooden component into the wormhole, and the filling is completed by curing for 24h to 48h at a temperature of 10℃ to 25℃ and a humidity of 20% to 50%.